Knowledge and attitudes toward nutritional deficiencies in celiac disease among medical students and healthcare providers in Egypt - Mohammed N. Abdelaziz; Hajer Azzam; Abdalla Hefnawy; Ahmed R. A. Moustafa; Hager G. Elkasabi; Abdelmalek Elkasabi; Omar Abdallah (Scientific Reports, 2025)
Abstract Celiac disease is an autoimmune enteropathy caused by gluten intake in foods and cereals. Weight loss, persistent diarrhea, and starvation are all possible outcomes. A lack of awareness about CD and malnutrition among medical students and healthcare professionals can result in inadequate nutritional guidance and delayed diagnoses, ultimately compromising patient outcomes and treatment adherence. Greater education and training programs for medical students can help alleviate these concerns and enhance patient outcomes. This study aims to assess the level of knowledge, attitude, and practice regarding nutritional deficiencies related to celiac disease among medical students and healthcare providers in Egypt. The secondary outcome is to identify knowledge gaps and potential barriers to effective implementation. This was a questionnaire-based cross-sectional study. The targeted population included students enrolled in any Egyptian medical institution during the academic year 2024–2025, as well as healthcare providers. The questionnaire included sections on demographic information, knowledge about celiac disease and nutritional deficiencies, and attitudes towards nutritional management of celiac disease. Using a convenient sampling method, it was distributed electronically in the English language. A total of 1233 people participated in the study. The median knowledge of celiac disease was 13, indicating that only 11% of individuals had adequate understanding of the condition (8–19). The median knowledge of women and those who lived in cities was higher (p = 0.003 and ←0.001, respectively). Physicians in internal medicine had a greater median level of expertise than pediatricians, indicating a significant difference in specialty among healthcare practitioners (p = 0.01). Only 11.9% of participants demonstrated sufficient understanding of the nutritional inadequacies linked to a gluten-free diet. The median knowledge of women and non-Egyptian individuals was higher (p = 0.05 and 0.03, respectively). Different governorate regions had significantly different knowledge medians (p = 0.002), with Delta governorates having a higher median than Greater Cairo (p = 0.004). This study highlighted the gap in CD knowledge among Egyptian medical students and healthcare providers, particularly concerning symptoms, diagnostic methods, and dietary management.